The Potential for Electrofuels Production in Sweden Utilizing Fossil and Biogenic CO2 Point Sources - Hansson, Julia; Hackl, Roman; Taljegard, Maria; Brynolf, Selma; Grahn, Maria (Frontiers in Energy Research, 2017)
This paper maps, categorizes, and quantifies all major point sources of carbon dioxide (CO2) emissions from industrial and combustion processes in Sweden. The paper also estimates the Swedish technical potential for electrofuels (power-to-gas/fuels) based on carbon capture and utilization. With our bottom-up approach using European databases, we find that Sweden emits approximately 50 million metric tons of CO2 per year from different types of point sources, with 65% (or about 32 million tons) from biogenic sources. The major sources are the pulp and paper industry (46%), heat and power production (23%), and waste treatment and incineration (8%). Most of the CO2 is emitted at low concentrations (<15%) from sources in the southern part of Sweden where power demand generally exceeds in-region supply. The potentially recoverable emissions from all the included point sources amount to 45 million tons. If all the recoverable CO2 were used to produce electrofuels, the yield would correspond to 2–3 times the current Swedish demand for transportation fuels. The electricity required would correspond to about 3 times the current Swedish electricity supply. The current relatively few emission sources with high concentrations of CO2 (>90%, biofuel operations) would yield electrofuels corresponding to approximately 2% of the current demand for transportation fuels (corresponding to 1.5–2 TWh/year). In a 2030 scenario with large-scale biofuels operations based on lignocellulosic feedstocks, the potential for electrofuels production from high-concentration sources increases to 8–11 TWh/year. Finally, renewable electricity and production costs, rather than CO2 supply, limit the potential for production of electrofuels in Sweden.